Predominance of Metabolic Resistance in a Six-Way-Resistant Palmer Amaranth (Amaranthus palmeri) Population - Shyam, Chandrima; Borgato, Ednaldo A.; Peterson, Dallas E.; Dille, Johanna Anita; Jugulam, Mithila (Frontiers in Plant Science, 2021)
Evolution of multiple herbicide resistance (MHR) in Palmer amaranth across the USA is a serious challenge for its management. Recently, a Palmer amaranth population (KCTR; Kansas Conservation Tillage Resistant) from a long-term conservation tillage research project in Kansas, USA, was found uncontrolled by several commonly used herbicides. Importantly, this field did not have a history of repeated use of some of the herbicides for which the KCTR Palmer amaranth population showed lack of control. The objectives of this study were to confirm the evolution of multiple resistance and determine possible mechanism(s) of resistance in KCTR Palmer amaranth. In response to postemergence application, 30 to 100% of KCTR Palmer amaranth survived field recommended rates of 2,4-D, ALS-, PS II-, EPSPS-, PPO-, HPPD-inhibitors, or tank- or pre-mixture of PS II- and HPPD-inhibitors, confirming evolution of six-way resistance in this Palmer amaranth population. However, this population was found susceptible to the PS I- and glutamine synthetase inhibitors. Chlorsulfuron- and atrazine-resistant plants did not show any previously reported mutation in ALS and psbA genes, the target sites of these herbicides, respectively. However, the survivors of glyphosate treatment showed amplification of EPSPS gene (up to 88 copies). The KCTR plants pretreated with cytochrome P450- or GST-inhibitors along with atrazine, 2,4-D, lactofen, or mesotrione had significantly less biomass accumulation than those treated with herbicides alone. Plants treated with P450-inhibitor followed by imazethapyr showed moderate reduction of biomass in KCTR which was statistically similar to a susceptible Palmer amaranth biotype (MSS) treated with imazethapyr. These results suggest predominance of metabolic resistance possibly mediated by cytochrome P450 and GST enzyme activity that may have predisposed KCTR Palmer amaranth population to evolve resistance to multiple herbicides. This is the first report of evolution of six-way resistance in a single Palmer amaranth population. Appropriate management strategies, including integration of cultural, mechanical and herbicide mixtures, are warranted to control such Palmer amaranth populations.